A call to act: RN volunteers needed in their communities. Issue 2 (13th December 2019) - LoGrippo, Maria Torchia; Brienza‐Arcilla, Diane; Vaid Raoji, Nina; Polakowski, Jennifer
Abstract: Objective: Recognizing registered nurses (RNs) as valued, trusted professionals to lead and advocate for healthier communities (Pittman, 2019), the New Jersey Action Coalition (NJAC) developed a model designed to match RN volunteers to community projects. Design: Using a descriptive study design, researchers examined the numbers of RN volunteers and projects across 21 counties in NJ from 2016 to 2018. Sample: The sample consisted of the numbers of volunteers and projects from every county retrieved from the NJAC's website. Measurements: In addition to the NJAC data, researchers examined the percentage of RNs living in each county as well as data from County Health Rankings & Roadmaps© (University of Wisconsin Population Health Institute, 2019). The counties were divided into three groups: high, moderate, and low overall health counties. Results: After 2 years of implementing the NJAC model, the data revealed that, at minimum, there was one RN coach per county in the high overall health counties group. In the lower overall health counties group, there were fewer community projects, less RN coaches, and volunteers. Conclusion: Engaging RN volunteers requires raising awareness of the needs of the community and the ways in which a RN can take action to promote public health and health equity.